2023
DOI: 10.3390/agronomy13061558
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Effects of Fencing Enclosure on Soil Quality Based on Minimum Data Set in Biru County of the Qinghai–Tibet Plateau, China

Abstract: Fencing enclosures play an important role in improving ecological quality. There is a direct impact of implementing fencing enclosures on the change in soil quality. The soil quality index was used to examine the effects of fencing enclosures for different years (7 and 11 years) on soil quality in Biru County of Qinghai–Tibet Plateau, China. The fencing enclosure significantly increased soil water content, non-capillary porosity, soil organic matter, total nitrogen, total phosphorus, and alkali-hydrolyzable ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 60 publications
2
4
0
Order By: Relevance
“…Land use change had significant effects on soil property contents in different regions and nations [18,22]. Our results confirmed the findings that land use change in karst regions significantly changed the contents of different soil properties (Table 1).…”
Section: Effect Of Land Use Types On Soil Propertiessupporting
confidence: 89%
See 4 more Smart Citations
“…Land use change had significant effects on soil property contents in different regions and nations [18,22]. Our results confirmed the findings that land use change in karst regions significantly changed the contents of different soil properties (Table 1).…”
Section: Effect Of Land Use Types On Soil Propertiessupporting
confidence: 89%
“…The PCA analysis was an effective method for reducing redundant information and selecting useful information. This method is commonly used for selecting the MDS for SQ assessment [2,18]. The cumulative variance of the chosen PCs exceeded 92%, which indicated that the two PCs could reflect the variability of the twelve soil properties, and they could be used to choose the key soil indicators in MDS.…”
Section: Evaluation Of Sq Using Different Soil Quality Indexesmentioning
confidence: 99%
See 3 more Smart Citations